Analisis Kandungan Sulfur pada Air Panas di Kaki Gunung Desa Sedoa Kecamatan Lore Utara Kabupaten Poso - Meilan Kristina Pogoa; Tahril Tahril (Media Eksakta, 2021)
Research on the Sulfur Content Analysis in the Hot Springs at the Foot of the mountain in Sedoa Village, North Lore District, Poso Regency has been conducted. The purpose of this study was to determine the sulfur content in the hot springs at the foot of the mountain in Sedoa Village, North Lore District, Poso Regency. The method used is the Gravimetric method. Hot water samples were taken in the morning and allowed to stand for 3 hours, 1 day, 2 days, and 3 days with 3 different sampling points. Point A is hot water consumed by the community, points B and C are hot water used by the community for bathing and washing. The results showed that the sulfur content of sample A for 3 hours was 9 mg/L, sample B was 4.5 mh/L, sample C was 4.5 mg/L. For 1 day, sample A was 4.5 mg/L, sample B was 4.5 mg/L, sample C was 4.5 mg/L. For 2 days, sample A was 4.5 mg/L, sample B was 4.5 mg/L, sample C was 4.5 mg/L. For 3 days, sample A was 4.5 mg/L, sample B was 4.5 mg/L, sample C was 4.5 mg/L. Sulfur content in the hot springs in Sedoa Village ranges from 4.5 mg/L – 9 mg/L. This level is far below the standard sulfur content, which is <400 mg/L.